â€œIs it True That The Soil Contains Air?â€ (Improving The Conceptual Understanding of 5th Graders Through POE Strategy) - Desiyanti, Tintin; Suhandi, Andi; Sopandi, Wahyu; Novianti, Ersa (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
The use of POE strategies in Indonesia has been widely developed in learning activities at junior and senior high school levels, but is still rarely used at the elementary level. Facts on the ground show that students' understanding of science concepts about air containing soil is still low. Based on this situation, this study aims to determine the increase in the ability to understand the concept that soil contains air in fifth grade students in one elementary school in Bandung. The POE strategy syntax consists of activities: predict, observe, and explain. The research design used was one group pretest posttest design. Sampling is done using non-random sampling techniques. The number of research samples consisted of 28 elementary students. Research data were collected using a four-tier diagnostic type test. Data analysis is performed by looking at the level of understanding changes by category: construction, revision, complementation, static, and disorientation. From this study, the results obtained that students tend to make improvements (revision) understanding of the concept of soil containing air after participating in learning activities with the POE strategy